Risk of disease progression in asymptomatic multiple myeloma - Dimopoulos, M.A.; Moulopoulos, A.; Smith, T.; Delasalle, K.B.; Alexanian, R. (The American Journal of Medicine, 1993)
Purpose: In recent years, increasing numbers of patients with asymptomatic multiple myeloma have been diagnosed by chance and followed without any therapy. Those at risk for early or late disease progression should be distinguished in order to prevent complications. This study defined prognostic factors that would predict the need for early treatment. Patients and Methods: We followed 95 patients with asymptomatic multiple myeloma without chemotherapy between 1974 and 1991. Magnetic resonance imaging (MRI) of the spine was conducted in 23% of patients with normal radiographs. An increase in serum myeloma protein to more than 50 g/L or new lytic bone lesions justified the institution of chemotherapy. Response to treatment and survival were assessed, and prognostic factors were defined for early or late disease progression by standard techniques. Results: The median time to progression in all patients was 26 months. The 25 patients with either a lytic bone lesion, or both serum peak greater than 30 g/L and Bence Jones proteinuria, had the shortest median time to progression of 10 months; the 27 patients without any harmful factor remained stable for a median of 61 months. MRI confirmed bone or marrow disease in half of the patients with normal radiographs and may assist in the prognostic staging. Despite the markedly different times of disease stability, the response rates and survival after chemotherapy were similar for all groups of patients. Conclusion: Among asymptomatic patients with multiple myeloma, the extent of disease at diagnosis and the subsequent rate of disease evolution were major factors in the total survival time. These patients are a markedly heterogeneous group who may benefit from different approaches to treatment according to defined risk factors. © 1993.